2007
DOI: 10.1002/bip.20681
|View full text |Cite
|
Sign up to set email alerts
|

One‐dimensional self‐assembly of a rational designed β‐structure peptide

Abstract: Fabricating various nanostructures based on the self-assembly of diverse biological molecules is now of great interest to the field of bionanotechnology. In this study, we report a de novo designed peptide (T1) with a preferential beta-hairpin forming property that can spontaneously assemble into nanofibrils in ultrapure water. The nanofibrils assembled by T1 could grow up to tens of microns in length with a left-handed helical twist and an average height of 4.9 +/- 0.9 nm. Moreover, protofilaments and nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 97 publications
3
21
0
Order By: Relevance
“…At high magnification the globules were counted showing a distribution on diameters centered in the range of 40-60 nm, as shown in the histogram there reported. On the basis of the intermediate steps reported for fibrillogenesis [21][22][23] we could say that when Leu is the first amino acid of the repeat sequence it has an impeding influence on the kinetics of fiber growth.…”
Section: Afm and Xps On Poly(leuglyglyvalgly) Deposits From Fresh Susmentioning
confidence: 99%
“…At high magnification the globules were counted showing a distribution on diameters centered in the range of 40-60 nm, as shown in the histogram there reported. On the basis of the intermediate steps reported for fibrillogenesis [21][22][23] we could say that when Leu is the first amino acid of the repeat sequence it has an impeding influence on the kinetics of fiber growth.…”
Section: Afm and Xps On Poly(leuglyglyvalgly) Deposits From Fresh Susmentioning
confidence: 99%
“…c Calculated by Expasy Molecular biology server. d Calculated according to the method of Bigelow(22).…”
mentioning
confidence: 99%
“…In a neutral aqueous solution, the intermolecular hydrophobic clustering and electrostatic interactions could act as driving forces, promoting peptide aggregation [21,22]. The entropy loss induced by peptide aggregation could be compensated by the release of the peptide-binding water into aqueous solutions, which could result in an increase of the system entropy in favor of peptide aggregation.…”
Section: Peptide Aggregationmentioning
confidence: 98%
“…We have previously reported that a de novo designed peptide T1 (sequence: RGYFWAGDYNYF), with -hairpin forming potential, is able to spontaneously assemble into homogeneous nanofibrils in an aqueous solution [21,22]. It has been demonstrated that, during T1 fibrogenesis, the peptide molecules undergo a significant conformational conversion from a random coil to a -structure, and the aromatic stacking plays important roles in both intra-and intermolecular interactions.…”
Section: Introductionmentioning
confidence: 98%